THE INTENTIONS TO ADOPT E-LEARNING USING UTAUT-3 MODEL: A POST COVID-19 PERSPECTIVE - Mahmood A Hussain Akbar; Mohd Helmi Ali; Mazzlida Mat Deli; Haytham Alawi (International Journal of Business and Society, 2023)
The COVID-19 pandemic has led to significant changes to e-learning systems, highlighting the importance of understanding the factors affecting their adoption. This study highlights the importance of e-learning by blending UTAUT (Unified Theory of Acceptance and Use of Technology) and UTAUT-3 theories to examine post-COVID adoption in e-learning programs. The purpose of this study is to investigate the influence of effort expectancy, performance expectancy, social influence, and facilitating conditions on the use of behavioral intentions in e-learning and the relationship between behavioral intentions and e-learning adoption behavior. The study sample consisted of 303 university students who continued to use e-learning systems after the COVID-19 pandemic, collected using a convenience sampling technique. Partial least squares structural equation modeling (PLS-SEM) through SmartPLS was used to analyze the collected data. The results revealed that effort expectancy, performance expectancy, and social influence significantly influence the behavioral intention to use e-learning. In contrast, the relationship between behavioral intention to use e-learning and acceptance of e-learning use is not significant. This study proved that significant changes in e-learning systems caused by the COVID-19 pandemic, and these changes are likely to continue after the pandemic. The study’s findings can help learners, learning providers, and policymakers plan and execute their online strategies.